Postharvest application of salicylic acid to improve the shelf life and quality of loquat (Eriobotrya japonica L.) fruit - Hussain, Zahoor; Hussain, Shaukat; Sarwar, Ghulam; Latif, Muhammad; Anwar, Raheel; Khadija, Faheem; Bilal, Muhammad; Sherani, Javeria; Yaseen, Muhammad (Journal of Pure and Applied Agriculture, 2023)
Loquat (Eriobotrya japonica L.) is an important sub-tropical fruit with very limited post-harvest life. Loquat fruit is a sweet acidic fruit and rich in natural antioxidants. Loquat is an important member of the family Rosaceae and the genus is Eriobotrya. Loquat is a potentially important minor commercial fruit as well as medicinal use and other purposes. Therefore, in the current study, we investigated the impact of salicylic acid treatments on the quality and shelf life of loquat fruit. Fresh harvest loquat fruits were treated with various concentrations of salicylic acid (SA) viz. 1500, 2500 and 3000 ppm for 2 minutes and were kept at room temperature (30 ± 2 oC) for 5 and 10 days. Untreated fruits were kept as control. The results showed that fruit treated with 3000 ppm salicylic acid exhibited minimum fruit weight loss (12.09 %), external browning (8.17 %), and internal browning (7.80%) after 10 days of shelf-life in contrast with control fruit. The highest total soluble solids contents (12.05% and 13.17%) were found in fruit treated with 1500ppm salicylic acid with respect to other treatments of SA. In conclusion, between the tested treatments, application of the highest level of salicylic acid (3000 ppm) effectively maintained the external and external browning. © 2021 Department of Agricultural Sciences, AIOU